If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -3x = -7x + -48 Reorder the terms: 12 + -3x = -48 + -7x Solving 12 + -3x = -48 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. 12 + -3x + 7x = -48 + -7x + 7x Combine like terms: -3x + 7x = 4x 12 + 4x = -48 + -7x + 7x Combine like terms: -7x + 7x = 0 12 + 4x = -48 + 0 12 + 4x = -48 Add '-12' to each side of the equation. 12 + -12 + 4x = -48 + -12 Combine like terms: 12 + -12 = 0 0 + 4x = -48 + -12 4x = -48 + -12 Combine like terms: -48 + -12 = -60 4x = -60 Divide each side by '4'. x = -15 Simplifying x = -15
| 7x+10+5x-8x= | | 6x+33=14x-63 | | 6q+5q= | | -3q=5 | | (5x-22)(2x+35)= | | -8.4=c-3.1 | | 4.4=c+0.7 | | z^2+27=12z | | 7x^2+6x-2=0 | | x^2+27=12z | | 7q-5=10q+19 | | 3x+5-2=2x+12 | | 3p+5=j | | (2x+1)(4x^2+27x-7)=0 | | 10(x-4)=8x-32 | | 4x^2+32x=192 | | .5(h+5)(h)=18 | | 2x^3+6x=-7x^2 | | 6(b-4)=30 | | 25=.5(h*h+8) | | (-11x^2y^2)(-6xy^5)= | | 6x^2+17x+7= | | 3a^3-36a^2+81a=0 | | 3x^2+7X-15=0 | | (3x)(-2x^5)= | | 4x^0y= | | 6(6x-7)(3x+7)=0 | | -37+(-48)=d | | 9y-4x=12 | | -8(x+3)=8-7x | | 4m^2+7m=25 | | -2(4x-3)=4x |